Investigation of Melamine Presence in Canned Tuna Fish by Capillary Zone Electrophoresis Method - Aysel Bayhan Öktem; Buket Er Demirhan; Burak Demirhan; Gülderen Yentür; Sezen Yarımkaya Baş (Journal of Agricultural Sciences, 2015)
Melamine is widely used as a chemical in food industry and may lead to kidney damage. The aim of this study was to determine melamine and pH value of 80 canned tuna fish samples of four different brands (A, B, C, D) sold in Ankara, Turkey. Quantitative determination of melamine in canned tuna fish samples was carried out by capillary zone electrophoresis with diode array detector (CZE-DAD). The limits of detection and quantitation for melamine were found to be 0.21 mg kg-1and 0.68 mg kg-1, respectively. The proposed method was successfully applied for the analysis of melamine in canned tuna fish samples by mean recovery with 104.7% in oily and 107.6% for light samples. Melamine levels were found as <0.68 mg kg-1 (LOQ value) in all samples analysed during the period of the study. The mean pH values (±SE) of the samples for the A, B, C and D brands were determined to be 5.89 ± 0.02, 5.86 ± 0.01, 5.83 ± 0.02 and 5.82 ± 0.02, respectively. As a result, present study shows that the presence of melamine of canned tuna fish obtained during the period of study do not pose a health risk to consumers.Keywords: Capillary zone electrophoresis; Fish; Melamin